2022
DOI: 10.1093/humrep/deab284
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular function in 8- to 9-year-old singletons born after ART with frozen and fresh embryo transfer

Abstract: STUDY QUESTION Do 8- to 9-year-old singletons conceived after frozen embryo transfer (FET) or fresh embryo transfer (Fresh-ET) have increased arterial stiffness compared to naturally conceived (NC) children? SUMMARY ANSWER The process of FET or Fresh-ET is not associated with altered cardiovascular function in 8- to 9-year-old singletons, including arterial stiffness, as compared to NC children. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 62 publications
0
9
0
1
Order By: Relevance
“…An increase in markers of the metabolic syndrome in childhood and adolescence, such as central obesity, hypertension, glucose intolerance, insulin resistance and dyslipidaemia, often persist into adulthood and translate to an increased risk of diabetes and cardiovascular disease in adulthood ( Bao et al , 1994 ; Chen et al , 2000 ). Despite some studies reporting an increased risk of unfavourable cardiometabolic and cardiovascular outcomes in offspring conceived after ART, other, recent studies do not demonstrate such an increased risk in those conceived after ART ( Shiloh et al , 2019 ; Juonala et al , 2020 ; Mizrak et al , 2022 ).…”
Section: Introductionmentioning
confidence: 91%
“…An increase in markers of the metabolic syndrome in childhood and adolescence, such as central obesity, hypertension, glucose intolerance, insulin resistance and dyslipidaemia, often persist into adulthood and translate to an increased risk of diabetes and cardiovascular disease in adulthood ( Bao et al , 1994 ; Chen et al , 2000 ). Despite some studies reporting an increased risk of unfavourable cardiometabolic and cardiovascular outcomes in offspring conceived after ART, other, recent studies do not demonstrate such an increased risk in those conceived after ART ( Shiloh et al , 2019 ; Juonala et al , 2020 ; Mizrak et al , 2022 ).…”
Section: Introductionmentioning
confidence: 91%
“…Other metabolic factors, such as low-density lipoprotein cholesterol levels, BMI, and fasting insulin, were comparable (51). Although other more recent studies reported no differences in cardiometabolic parameters between ART and non-ARTconceived offspring (11, 13,14), in our GUHS study 163 ART of offspring at 17 years of age replicated the assessments previously completed by the 1,457 participants in the Raine study at a similar age (52). The ART offspring females had a lower BMI, thinner skinfolds, and less subcutaneous fat, than the Raine participants, whereas males were not significantly different.…”
Section: Cardiometabolic Healthmentioning
confidence: 67%
“…For example, various childhood studies have demonstrated an increase in systolic and diastolic blood pressure, adiposity, vascular dysfunction, as well as unfavourable lipid and glucose profiles (10). However, more recent studies report no differences, or indeed favourable cardiometabolic outcomes, for ART-conceived offspring (11)(12)(13)(14). However, studies performed on adolescents are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…[71][72][73][74] A recent study including 8-9-year-old conceived after frozen, fresh embryo transfer and natural conceived children report no differences regarding arterial stiffness assessed from blood pressure and aortic ascendant distensibility between groups reported also no altered cardiovascular function. 75 Results that seem reassuring.…”
Section: Assisted Reproductive Technologiesmentioning
confidence: 99%